2009
DOI: 10.2527/jas.2008-1476
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of heifers offered ad libitum or restricted access to feed for a one hundred forty-day period after weaning1

Abstract: Reproductive performance was evaluated in composite heifers born over a 3-yr period that were randomly assigned to control (fed to appetite; n = 205) or restricted (fed at 80% of that consumed by controls adjusted to a common BW basis; n = 192) feeding for a 140-d period, beginning about 2 mo after weaning at 6 mo of age and ending at about 12.5 mo of age. Heifers were fed a diet of 67% corn silage, 18% alfalfa, and 9% of a protein-mineral supplement (DM basis). Restricted heifers consumed 27% less feed over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 22 publications
11
61
2
6
Order By: Relevance
“…Conversely, the proportion of heifers becoming pregnant during the first 21 d of the breeding period was less for low-vs. high-gain heifers; thus, reducing heifer growth and body condition during the prepubertal and pubertal periods may potentially delay fertility. These observed effects of decreased dietary energy and development to 55% of mature BW on pregnancy rate concur with results from previous studies in which restricting feed during development reduced pregnancy rate to synchronized AI at initiation of the breeding period (Roberts et al, 2009), but final pregnancy rates did not differ between BW gain groups (Funston and Deutscher, 2004;Martin et al, 2008;Roberts et al, 2009). Reduced fertility in the present study was not due to delayed initiation of ovarian cyclicity, for 97% of the heifers had ovulated by 21 d of breeding in 2010 and 2011.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Conversely, the proportion of heifers becoming pregnant during the first 21 d of the breeding period was less for low-vs. high-gain heifers; thus, reducing heifer growth and body condition during the prepubertal and pubertal periods may potentially delay fertility. These observed effects of decreased dietary energy and development to 55% of mature BW on pregnancy rate concur with results from previous studies in which restricting feed during development reduced pregnancy rate to synchronized AI at initiation of the breeding period (Roberts et al, 2009), but final pregnancy rates did not differ between BW gain groups (Funston and Deutscher, 2004;Martin et al, 2008;Roberts et al, 2009). Reduced fertility in the present study was not due to delayed initiation of ovarian cyclicity, for 97% of the heifers had ovulated by 21 d of breeding in 2010 and 2011.…”
Section: Discussionsupporting
confidence: 81%
“…Historically, replacement heifers are fed a diet to achieve 65% of mature BW by 14 mo of age (Patterson et al, 1992), whereas purebred beef heifers fed to 55% of mature BW had increased dystocia and calf mortality and decreased fertility after first calving. Conversely, recent studies found that feeding crossbred beef heifers to 50% to 55% of mature BW reduced body size and development costs without compromising pregnancy rate (Funston and Deutscher, 2004;Martin et al, 2008;Roberts et al, 2009). Thus, it is hypothesized that developing beef heifers to achieve 55% vs. 65% of mature BW at breeding on less dietary energy and ADG (0.45 vs. 0.80 kg/d) will not affect ovarian development or compromise fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Heifers grazing on natural pastures fed supplement presented 4.05±3.58 cm 2 and 0.43±0.08 mm higher UREA and UBFT values, respectively, on October 18, compared with the non-supplemented heifers. These results are in agreement with the findings of Roberts et al (2009), who also observed that feed restriction reduced the UREA (4.70 cm²) and UBFT (0.68 mm) values of nonsupplemented heifers relative to supplemented heifers. The supplementation of heifers grazing on both natural pasture and on ryegrass promoted better muscling (Tables 2 and 3), represented by rib eye area (UREA).…”
Section: Discussionsupporting
confidence: 83%
“…The NRC (1996) recommends a target BW of 60% mature cow weight at the beginning of the breeding season to obtain high reproduction rates. However, studies carried out in the last decades comparing intensive with extensive systems found that lower target weights (50-57% of the mature weight) reduce production costs and do not negatively affect reproductive performance (Funston and Deutscher, 2004;Roberts et al, 2009;Funston and Larson, 2011;Mulliniks et al, 2013). Considering that the geographical region of the farm and the applied production system do not allow for heavy mature and weaning weights, heifers need to achieve a higher percentage of the mature weight of a cow to reach puberty.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Larson et al (2011) reported increased body weight after corn residue administration for winter grazing. Early post-weaning growth has a more profound effect on reproductive success in the first breeding season, indicating that weaning weight has a major impact on timing of puberty (Roberts et al, 2009) and can be consistently induced by a high-energy diet of beef heifers (Gasser et al, 2006). Banta et al (2005) observed that two-year-old cows subjected to early weaning showed 92% of estrus appearance and 71% of conception rates, demonstrating that increasing energy intake of cows through early weaning should result in decreased postpartum interval and increased pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%